The Profile of Students’ Learning Difficulties in Concepts Mastery in Calculus Course - Wewe, Melkior (Desimal: Jurnal Matematika, 2020)
This research was conducted because of the low students’ learning outcomes in concepts mastery in calculus course. The purpose of this research was to obtain the concepts mastery profile of the second semester students of the Mathematics Education Study Program. The results obtained in this study were used as reference materials for calculus course and to influence the lecturers to find the right approach or learning model in order to improve students’ concept mastery. This study employed the descriptive-quantitative method. The results showed that the students' were having learning difficulties in concepts mastery in calculus course. The learning difficulties were caused by low concepts mastery and low mathematical principles understanding that led the students into wrong process skills. The difficulties experienced by the students such as difficulties in understanding the concepts and principles of the absolute value of the material, limit functions, and derivatives so that their answers were not as expected.